Medical Marijuana programs: Implications for cannabis control policy – Observations from Canada - Fischer, Benedikt; Kuganesan, Sharan; Room, Robin (The International journal of drug policy, 2015)
•Cannabis use is prevalent, and traditionally controlled by prohibition, in Canada.•In 2001, a ‘medical marijuana’ (MM) access program was created for severely ill people.•While the government rejects general reform, new MM rules were implemented in 2014.•Doctors can authorize MM for any health problem, to be supplied by licensed producers.•New MM regulations constitute ‘de facto’ legalization under a veil of ‘medicalization’. While prohibition has been the dominant regime of cannabis control in most countries for decades, an increasing number of countries have been implementing cannabis control reforms recently, including decriminalization or even legalization frameworks. Canada has held out from this trend, although it has among the highest cannabis use rates in the world. Cannabis use is universally criminalized, and the current (conservative) federal government has vowed not to implement any softening reforms to cannabis control. As a result of several higher court decisions, the then federal government was forced to implement a ‘medical marijuana access regulations’ program in 2001 to allow severely ill patients therapeutic use and access to therapeutic cannabis while shielding them from prosecution. The program's regulations and approval processes were complex and subject to extensive criticism; initial uptake was low and most medical marijuana users continued their use and supply outside the program's auspices. This year, the government introduced new ‘marijuana for medical purposes regulations’, which allow physicians to ‘authorize’ medical marijuana use for virtually any health condition for which this is considered beneficial; supply is facilitated by licensed commercial producers. It is expected that some 500,000 users, and dozens of commercial producers will soon be approved under the program, arguably constituting – as with medical marijuana schemes elsewhere, e.g. in California – de facto ‘legalization’. We discuss the question whether the evolving scope and realities of ‘medical cannabis’ provisions in Canada offer a ‘sneaky side door’ or a ‘better third way’ to cannabis control reform, and what the potential wider implications are of these developments.